(untitled) (Journal of Applied Learning and Teaching, 2025)
English serves as a pivotal subject in Indian school curricula, offering students a platform to connect with diverse global and cultural perspectives. The National Education Policy (NEP) 2020 emphasizes revitalizing India’s rich cultural heritage by integrating the Indian Knowledge System (IKS) into education. This study employs the Content Analysis method to critically examine the representation of IKS in English textbooks prescribed by the Central Board of Secondary Education (CBSE) and the Rajasthan Board of Secondary Education (RBSE). The findings reveal significant discrepancies in the extent and depth of IKS incorporation between the two boards, with CBSE textbooks demonstrating limited engagement compared to the more localized emphasis in RBSE curricula. These inconsistencies underscore the challenges of decolonizing education and the persistent dominance of capitalistic pedagogies that prioritize market-driven objectives over cultural and ecological sustainability. The study advocates for the effective implementation of NEP 2020 recommendations through green curricular reforms that prioritize IKS integration, social justice, and sustainability. By aligning education with holistic and equitable frameworks, these reforms can empower students as agents of cultural preservation and ecological stewardship, fostering a globally connected yet culturally rooted education system.